2016
DOI: 10.1007/s13353-016-0344-7
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations and genome-wide associations reveal putative genes and metabolic pathways involved with the feed conversion ratio in beef cattle

Abstract: The use of genome-wide association results combined with other genomic approaches may uncover genes and metabolic pathways related to complex traits. In this study, the phenotypic and genotypic data of 1475 Nellore (Bos indicus) cattle and 941,033 single nucleotide polymorphisms (SNPs) were used for genome-wide association study (GWAS) and copy number variations (CNVs) analysis in order to identify candidate genes and putative pathways involved with the feed conversion ratio (FCR). The GWAS was based on the Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 71 publications
(89 reference statements)
0
25
0
Order By: Relevance
“…Similarly, candidate genes in pathways related to protein metabolism have been suggested in genomic regions accounting for feed conversion ratio in cattle [7]. Ribosome biogenesis and translation processes were notably enriched in over-expressed genes in tissues of pigs from the low RFI line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, candidate genes in pathways related to protein metabolism have been suggested in genomic regions accounting for feed conversion ratio in cattle [7]. Ribosome biogenesis and translation processes were notably enriched in over-expressed genes in tissues of pigs from the low RFI line.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some DNA variants playing a role in feed efficiency traits have been proposed from analyses of SNP locations by whole-genome association in pigs [4, 5] and beef cattle [6, 7]. Based on their genomic location in the vicinity of these SNPs, putative gene candidates for feed efficiency traits including RFI have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these pathways (Additional file 3) were related to nutrients (fatty acids, carbohydrates and proteins) and metabolism. de Almeida Santana et al (2016) [35] reported that the retinol metabolic pathway was involved in the feed conversion ratio in beef cattle in relation to rump fat thickness. The authors also discussed that lipid and protein metabolisms were well-known important factors in feed efficiency physiology.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also discussed that lipid and protein metabolisms were well-known important factors in feed efficiency physiology. The relationship between retinol metabolism and the feed conversion ratio phenotype in Nellore beef cattle has been previously described [36] and [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Another candidate region identified on OAR6:80.6-81.0 Mb (S7 Fig and Table 4), shown by the Ethiopian group (eleven breeds) and the Libyan Barbary and including the EPHA5 gene, was also detected in a GWAS for wool production traits in a Chinese Merino sheep population and reported to be significantly associated with fiber diameter [33]. Moreover, it has been identified through GWAS as a candidate gene for feed conversion ratio in Nellore cattle [34]. The signal on OAR7:33.5-33.9 Mb (S8 Fig and Table 4) was detected in the Barbaresca and Laticauda, as well as in a previous study [9].…”
Section: Discussionmentioning
confidence: 99%